The State and social organizations in Chile (Polis (Santiago), 2018)
Through an historical journey on the role of the state and civil society, the author posits that organizations and social movements in post-authoritarian state, due to the radical neo-liberal modernization and a political system of supervised democracy, there is no social space to have a political voice. The State accepts them, constrained to certain functions, but does not stimulate or favor their self-development. Given this, organizations must choose between submitting to this role, or seek self-development with all the difficulties and risks involved.
Keywords: state; civil society; neoliberal modernization; social organizations